2015
DOI: 10.3928/01477447-20151020-10
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss and Transfusion After Topical Tranexamic Acid Administration in Primary Total Knee Arthroplasty

Abstract: There has been much debate and controversy about the safety and efficacy of the topical use of tranexamic acid in primary total knee arthroplasty (TKA). The purpose of this study was to perform a meta-analysis to evaluate whether there is less blood loss and lower rates of transfusion after topical tranexamic acid administration in primary TKA. A systematic review of the electronic databases PubMed, CENTRAL, Web of Science, and Embase was undertaken. All randomized, controlled trials and prospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
(56 reference statements)
1
11
1
Order By: Relevance
“…Our results showed that compared to NS, TXA administration reduced postoperative RBC loss to 279.35 mL and hidden blood loss to 700.3 mL (assuming 30% hematocrit) in patients with intertrochanteric fractures. These results are consistent with previous studies reporting on total knee arthroplasty [ 12 ], periacetabular osteotomy [ 11 ], extracapsular fracture of the hip [ 13 ], and total shoulder arthroplasty [ 16 ]. Our data also suggests that TXA administration has the potential to decrease the number of orthopedic patients requiring transfusion; administration of 1 g of TXA decreased the transfusion rate from 56.09 to 28.20%.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that compared to NS, TXA administration reduced postoperative RBC loss to 279.35 mL and hidden blood loss to 700.3 mL (assuming 30% hematocrit) in patients with intertrochanteric fractures. These results are consistent with previous studies reporting on total knee arthroplasty [ 12 ], periacetabular osteotomy [ 11 ], extracapsular fracture of the hip [ 13 ], and total shoulder arthroplasty [ 16 ]. Our data also suggests that TXA administration has the potential to decrease the number of orthopedic patients requiring transfusion; administration of 1 g of TXA decreased the transfusion rate from 56.09 to 28.20%.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are reports of thrombus formation associated with IV TXA [ 16 , 17 ]. Topical TXA applications have been reported as another method to reduce blood loss and are associated with fewer systemic side effects compared to IV TXA [ 6 , 7 , 18 21 ]. Topical TXA is usually applied by soaking TXA in the operating field and washed after period of time or left to drain out following wound closure and drain insertion.…”
Section: Introductionmentioning
confidence: 99%
“…While TXA is known to be effective, patients with thromboembolic events and conditions often contraindicate its administration (35,40). Topical application of TXA is perhaps as effective as intravenous administration, and is not contraindicated (35,(43)(44)(45). Erythropoietin is an effective means of increasing preoperative Hb, but may not be cost effective (13).…”
Section: Discussionmentioning
confidence: 99%